Numerical Study on Acoustic Resonance Excitation in Closed Side Branch Pipeline Conveying Natural Gas - Liuyi Jiang; Hong Zhang; Qingquan Duan; Yulong Zhang (Shock and Vibration)
Flow-induced acoustic resonance in the closed side branch of a natural gas pipeline can cause intensive vibration which threatens the safe operation of the pipeline. Accurately modeling this excitation process is necessary for a workable understanding of the genetic mechanism to resolve this problem. A realizable k-ε Delayed Detached Eddy Simulation (DDES) model was conducted in this study to numerically simulate the acoustic resonance problem. The model is shown to accurately capture the acoustic resonance phenomenon and self-excited vibration characteristics with low calculation cost. The pressure pulsation component of the acoustic resonance frequency is gradually amplified and transformed into a narrowband dominant frequency in the process of acoustic resonance excitation, forming a so-called “frequency lock-in phenomenon.” The gas is pressed into and out of the branch in sinusoidal mode during excitation. The first-order frequency, single vortex moves at the branch inlet following the same pattern. A quarter wavelength steady standing wave forms in the branch. The mechanism and characteristics presented in this paper may provide guidelines for developing new excitation suppression methods.